Computação em nuvem: fatores que influenciam a adoção pelas empresas no Brasil - Vieira, Cláudia Simone (2017)
Cloud computing (CN) refers for sharing of computing resources, which can be combined with each other, such as data storage and communication, processing capacity (servers and memory), software, applications, and services. The CN differs from the public, private and hybrid deployment model and the service model known as 'as a service': infrastructure, platform and software. The objective of this research was to identify the factors that influence the adoption of cloud computing by the firms in Brazil. The proposed research model included perceived benefits and risks and perceived innovation attributes of the diffusion innovations theory (relative advantage, compatibility, observation, testing, and complexity) as exogenous latent variables and CN adoption as an endogenous latent variable. The research was applied to private companies through a questionnaire available on the internet and 135 responses were obtained, and PLS-PM (Partial Least Square - Path Modeling) was used. The results obtained indicated that the seven factors influence CN adoption, and the relative advantage, compatibility, observation, testing, and perceived benefits are positively associated with the adoption of NC and perceived complexity and risks are negatively associated to adoption. The perceived risks factor had the greatest influence on adoption, and the higher the risk the lower the adoption and vice versa. In this way, identifying and understanding the factors influencing CN adoption can help the actors (firms, suppliers, developers and others) involved in this process to take action and decisions according to their needs and strategies.